HUBUNGAN BEBAN KERJA DAN JAM KERJA DENGAN KELELAHAN KERJA KARYAWAN BAGIAN PRODUKSI CV. JAYA MANUNGGAL GARMEN - Yoga Bagaskara; JT Lobby Loekmono; Yustinus Windrawanto (Jurnal Mahasiswa BK An-Nur : Berbeda, Bermakna, Mulia, 2023)
This study aims to determine the significance of the relationship between workload and work fatigue and the significance of the relationship between working hours and work fatigue of employees of CV. Jaya Manunggal Garmen. This type of research is correlational in order to determine the relationship between workload variables and work hours variables with work fatigue variables. The population in this study were 45 employees of CV. Jaya Manunggal Garmen. The sample was taken using total sampling technique. Data collection techniques in this study used a scale and the data were analyzed using Kendall's tau_b technique. The research results obtained that there is a significant relationship between workload and employee fatigue with a significance of 0.000 <0.05 with a correlation coefficient value which shows the number 0.612. Furthermore, it was also found that there was a significant relationship between working hours and employee fatigue, as evidenced by a significance result of 0.000 <0.05 with a correlation coefficient value which shows the number 0.602